Reliability of Different RBC Indices and Formulas in the Discrimination of ?-Thalassemia Minor and Iron Deficiency Anemia in Surabaya, Indonesia - Yulia Nadar Indrasari1 , Yetti Hernaningsih1 , Munawaroh Fitriah1 , Arifoel Hajat1 , I Dewa Gede Ugr (Indian Journal of Forensic Medicine & Toxicology, 2021)
In this study, we evaluated the RBC indices in differentiating ?-thalassemia minor and iron deficiencyanemia in a healthcare center. This was an observational analytic study with a cross-sectional design usingblood specimens of children aged 3 years to 17 years with microcytic hypochromic anemia based onthe results of complete blood counts and evaluation of peripheral blood smears. Calculation of the RBCindices was performed as an initial screening to differentiate ?-thalassemia minor and iron deficiencyanemia. Iron profile examination and hemoglobin electrophoresis were performed to confirm the diagnosisof ?-thalassemia minor and iron deficiency anemia. The results of the independent samples t-test showedsignificant differences in Hb, MCV, MCH, and MCHC between ?-thalassemia minor and iron deficiencyanemia (p <0.05). The results of the Mann Whitney test showed a significant difference in the MentzerIndex to distinguish between ?-thalassemia minor and iron deficiency anemia (p <0.05). Also, the resultsof the independent samples t-test showed significant differences in the Green & King formula, Sirdah etal. formula, and the Maltos and Carvalho Index (p <0.05). The Green and King formula has a diagnosticsensitivity of 78.6% and a specificity of 76.6% and an accuracy of 78.03%. Various formulas based on theresults of complete blood count parameters have been developed to detect ?-thalassemia minor in areas witha high prevalence of ?-thalassemia with different sensitivity and specificity. In this study, it showed that theGreen and King formula has a diagnostic sensitivity of 78.6% and a specificity of 76.6%, and an accuracyof 78.03%. Green and King’s formula can be applied as an initial screening to differentiate ?-thalassemiaminor and iron deficiency anemia